Trends in breastfeeding and complementary feeding practices in Pakistan, 1990-2007 - Hanif Hafsa (BMC, 2011)
Abstract Background Breastfeeding and complementary feeding practices have profound implications for the maternal and child health status of a society. Feeding practices in Pakistan are suboptimal, leading to adverse outcomes on child health. In Pakistan, the Maternal, Neonatal and Child Health (MNCH) Program, in collaboration with several international organizations, including WHO and UNICEF, is working to improve these feeding practices in the country. The aim of this paper is to evaluate the effectiveness of these programs. Methods Estimates on the various indicators for infant and young child feeding proposed by WHO were analyzed in light of the Pakistan Demographic and Health Surveys (1990-91 and 2006-07) and several other national studies conducted since 1995. Results Nearly half the core and optional indicators have improved over the years, though modestly; the others have demonstrated no statistically significant improvement over the years. Of the five indicators required in the WHO tool for the assessment of infant and young child feeding, introduction of complementary foods, bottle-feeding, and early initiation of breastfeeding, stand in the poor category, while exclusive breastfeeding and duration of breastfeeding fall in the fair category, suggesting an overall poor status. Conclusions There is considerable scope to improve breastfeeding and complementary feeding in Pakistan. Further programs should focus on improving the following indicators that have shown no significant development: early initiation of breastfeeding, exclusive breastfeeding under six months, continued breastfeeding at two years, age appropriate feeding, and bottle feeding. Effective implementation of interventions that are known to improve breastfeeding practices is imperative, as is further research to yield data that can lead future endeavors.